Blockchain in accounting: A systematic review of financial reporting transparency and fraud mitigation in Indonesia - Arif Rahman Hasdik; Hidyatullah, Andi Muhammad Syukur; Nasaruddin, Nadya Annisa (Priviet Social Sciences Journal, 2026)
The crisis of public trust due to massive financial scandals demands a fundamental transformation in financial reporting architecture. Blockchain technology has emerged as a transformative solution owing to its decentralization, real-time transparency, and immutability. This study aims to analyze the implementation of blockchain in enhancing accounting transparency through a Systematic Literature Review (SLR) using the PRISMA 2020 protocol. The analysis was conducted on 42 high-quality articles filtered from Scopus, Sinta, and Garuda databases (2016–2026) and evaluated using the JBI Critical Appraisal instrument. The findings reveal three main mechanisms through which blockchain enhances transparency: Triple-Entry Accounting (TEA), real-time audit automation, and the reduction of information asymmetry. TEA introduces a layer of cryptographic verification ("trebit/hash") for each transaction, ensuring data immutability and reliability. In addition, smart contracts significantly reduce agency costs by automating compliance processes (i.e., compliance by design). In Indonesia, this adoption momentum is strengthened by the issuance of the Crypto Asset Implementation Bulletin by DSAK IAI (October 2025) and Financial Services Authority or Otoritas Jasa Keuangan (OJK) regulations regarding asset tokenization (September 2025). However, challenges such as high investment costs, gaps in accounting competencies, and infrastructure limitations outside urban areas remain significant barriers. This study contributes to the literature by providing an integrated framework that links technological mechanisms, regulatory readiness, and implementation challenges. It also recommends the development of specific Audit Standards (SA) for on-chain digital evidence to accelerate the transformation of the national digital accounting ecosystem.